2000
DOI: 10.1111/j.1572-0241.2000.2083_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic configuration and mucosal 5-aminosalicylic acid (5-ASA) concentrations in patients with crohn's disease: a GISC study

Abstract: The different mucosal concentrations in these two groups may be explained by the difference in segmental transit time induced by the different anastomotic configurations. A slower preanastomotic transit time, demonstrated in patients with end-to-side or side-to-side anastomosis, could offer a prolonged contact time between the intestinal content and the mucosa, resulting in an increase in drug absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On more detailed review, four more trials were excluded because comparison was not made between an SSA group and an EA group [24][25][26][27]. Three studies were excluded because the outcomes of interest were not suitably reported [28][29][30]. A further three studies were discarded because of overlap of the patient population [31][32][33].…”
Section: Study Selectionmentioning
confidence: 99%
“…On more detailed review, four more trials were excluded because comparison was not made between an SSA group and an EA group [24][25][26][27]. Three studies were excluded because the outcomes of interest were not suitably reported [28][29][30]. A further three studies were discarded because of overlap of the patient population [31][32][33].…”
Section: Study Selectionmentioning
confidence: 99%